2021
DOI: 10.3390/ijms22189939
|View full text |Cite
|
Sign up to set email alerts
|

Microcystin-LR (MC-LR) Triggers Inflammatory Responses in Macrophages

Abstract: We were the first to previously report that microcystin-LR (MC-LR) has limited effects within the colons of healthy mice but has toxic effects within colons of mice with pre-existing inflammatory bowel disease. In the current investigation, we aimed to elucidate the mechanism by which MC-LR exacerbates colitis and to identify effective therapeutic targets. Through our current investigation, we report that there is a significantly greater recruitment of macrophages into colonic tissue with pre-existing colitis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Other studies have shown that MC-LR induces the production of inflammatory cytokines and chemokines such as IL-6, MCP-1, and CXCL10, and activates innate immune responses in mouse testicular cells, leading to testicular inflammation [ 31 ]. MC-LR has also been shown to enhance TNF-α and IL-1β expression in mouse peritoneal macrophages, thus promoting M1 polarization [ 32 ]. Similarly, our study has shown that MC-LR enhanced the expression of TGF-β1 under the co-culture system.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that MC-LR induces the production of inflammatory cytokines and chemokines such as IL-6, MCP-1, and CXCL10, and activates innate immune responses in mouse testicular cells, leading to testicular inflammation [ 31 ]. MC-LR has also been shown to enhance TNF-α and IL-1β expression in mouse peritoneal macrophages, thus promoting M1 polarization [ 32 ]. Similarly, our study has shown that MC-LR enhanced the expression of TGF-β1 under the co-culture system.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-four hours after the challenge, the mice were euthanized, and their kidneys were snap-frozen at -85°C and prepared for RNA extraction (Figure 1). RNA was extracted using the RNeasy Plus Mini Kit (Cat # 74136, Qiagen) as previously described (14)(15)(16). A sequencing library for Poly (A) sequencing was prepared according to Illumina's mRNA sample preparation, followed by pairedended sequencing (14)(15)(16).…”
Section: The University Of Toledomentioning
confidence: 99%
“…RNA was extracted using the RNeasy Plus Mini Kit (Cat # 74136, Qiagen) as previously described (14)(15)(16). A sequencing library for Poly (A) sequencing was prepared according to Illumina's mRNA sample preparation, followed by pairedended sequencing (14)(15)(16). According to FastQC generated quality control information, low-quality, unknown, and contaminated bases/reads were removed.…”
Section: The University Of Toledomentioning
confidence: 99%
“…Exposure to MC-LR also resulted in greater increases in pro-inflammatory transcripts within colonic tissue (TNF-α, IL-1β, CD40, MCP-1) and the pro-fibrotic marker, PAI-1, as compared to DSS-only ingestion [ 57 ]. Mice with pre-existing colitis that were exposed to the toxin showed significantly higher macrophage infiltration in the colonic tissues as compared to the non-exposed mice [ 83 ]. Interestingly, the pro-inflammatory mediator CD40 was significantly upregulated on exposure to MC-LR, a molecular feature shared with IBD progression [ 84 ].…”
Section: Microcystins and Gut Healthmentioning
confidence: 99%